PERBEDAAN PENGARUH PENDEKATAN DAN PEMBELAJARAN DAN KEMAMPUAN GERAK TERHADAP HASIL BELAJAR SEPAK DAN TAHAN BOLA DALAM PERMAINAN SEPAKBOLA - Kodrad Budiyono (Universitas Tunas Pembangunan, 2011)
The differences of the studying approach effect and the motor ability to the result of the football studies and the defence of the ball in the football game (the experiment studies of the game learning approach and drill to the boy students of SD Muhammadiyah 3 Surakarta). Â This research is aimed to know: (1) the differences of the effect between the playing approach studies and drill to the result of the football game. (2) the differences of the effect of the football result studies and the defence of the ball between the students who have the high and low of the motor ability. (3) the effect of the interaction between the studying approach and the motor Â ability to the result of the football and the defence of the ball in football game. The method which used in this research is the experiment method with the factorial design 2x2. The population of the research is 60 boy students of SD Muhammadiyah 3 Surakarta, This sample of the research is 40 students, which is took by the purposive random sampling Data analysis techniques used in this research are two ways ANAVA followed by Newman-Kleus Range Test at significance level of Î¬ = 0.05. The result of the research shows that: (1) there are the differences of the signicant between the playing studying approach and drill to the result of the football studies and the defence of the ball. (2) there are the differences in the result of the football studies and theÂ defence of the ball which is significant between the students who have the high and low of the motor ability. (3) there are some effects between the interaction which is signicant between the playing approach studies and the level of the basic ability to the result of the football studies and the defence of the ball : (a) the students who have the high motor ability are more appropriate if they are given by the playing approach studies. (b) university students who have the motor ability are more appropriate if they are given by the drill of the approach studies.